Anemia in pregnancy: a prospective study of 100 cases - Pereira, Evith; Tambekar, Manisha (Tropical Journal of Pathology and Microbiology, 2019)
Background: Anemia in pregnancy is a major public health problem worldwide and is the most common hematological disorder during pregnancy. According to WHO, 35 to 75% of pregnant women in developing countries are anemic. Material and Methods: A prospective study was conducted among 100 pregnant women in their first trimester who attended antenatal clinic in a tertiary care hospital. Socio-demographic information were collected along with the blood samples. Hemoglobin concentration, blood indices, PCV, RDW, WBC and RBC counts were determined by a hematological auto-analyzer. Anemia was graded according to WHO criteria and morphological typing of anemia was done on the basis of peripheral blood smear examination. Result: A high prevalence (64%) of anemia was observed among 100 pregnant women of which majority had mild anemia (50%), moderate anemia (48.4%) and severe anemia (1.6%) commonly seen in younger age group (20-24 years). Factors such as age at marriage, age at first childbirth, illiteracy, gravida, working status, residence and socioeconomic status were found to be significantly. According to blood indices and peripheral blood smear analysis microcytic hypochromic anemia (59.4%) was the commonest morphological type of anemia followed by dimorphic anemia (23.4%). Iron deficiency anemia was found to be the commonest cause of anemia in pregnancy. Conclusion: The present study concluded that health education, good nutrition, thorough clinical and hematological examination with iron and folic acid supplements during antenatal period should be implemented to reduce the prevalence of anemia, thus decreasing maternal and fetal morbidity and mortality during pregnancy.